KEANEKARAGAMAN SERANGGA DAN LABA-LABA PADA PERTANAMAN PADI ORGANIK DAN KONVENSIONAL - Ardian Iman Pradhana; Gatot Mudjiono; Sri Karindah (Jurnal HPT (Hama Penyakit Tumbuhan), 2014)
ABSTRACTThe purpose of this research is to determine the effect of organic andconventional farming system to the diversity of insects and spiders in rice fields. The research was carried out in rice field of Sumber Makmur Farmer's Group andlaboratory of Entomology, Department of Plant Pests and Diseases BrawijayaUniversity. This research was conducted with observation method, observing the plots of organic and conventional rice field. Traps that used to take samples of insects and spiders in this research is farmcop. The number of insects and spiders that found inorganic fields higher than the conventional fields. Organic field has higher value ofdiversity index of insects and spiders than conventional field.Key words: Diversity, Insects, Spiders, Organic